Sociological perspective on the elimination of Karanganyar Regency as an impact of the 1930s economic depression - Teguh Hindarto; Chusni Ansori (SIMULACRA: JURNAL SOSIOLOGI, 2020)
The 1930s economic crisis in the United States had spread throughout the world and caused a number of social, economic, political and cultural impacts, including for the Dutch East Indies colonies. Karanganyar Regency, which was in the Bagelen Residency territory since 1901, had experienced the effects of the economic shock as well. Karanganyar was a district in the Kebumen Regency area. Before becoming a sub-district, Karanganyar was an independent regency and had its head of government from 1832 until 1936. Through literature studies, this paper intended to thoroughly analyze the existence of Karanganyar Regency in the colonial era, find out the background of its elimination, and the process of social change that occurred. To obtain the main variables that cause the elimination of Karanganyar Regency, the researcher utilized the historical comparative method. From the analysis, we concluded that the Economic Depression centred in the United States affected the Dutch East Indies colonies, particularly on the management of the government bureaucracy. This situation demanded the Dutch East Indies government to adapt to social change by removing a number of Regency, including Karanganyar Regency.